2013
DOI: 10.1007/s12639-013-0388-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Linguatula serrata nymphs in slaughtered sheeps in Isfahan province, southwest of Iran

Abstract: Linguatula serrata, well known as tongue worm; is an aberrant cosmopolitan parasite, which inhabits the carnivorous mammals (especially Canidae) respiratory system. The discharged eggs infect many plant feeder animals including human that produces visceral and nasopharyngeal linguatulosis which is known as Marrara syndrome in man. In current study, the prevalence rate of infection with L. serrata nymphs in mesenteric and mediastinal lymph nodes (MLNs) of slaughtered sheeps was investigated in Esfahan Province,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…It should be noted that in this research, mesenteric lymph nodes of the sheep were examined because it is the first site that the parasite chooses to enter (Shekarforush & Arzani-Shahni, 2002). However, based on other conducted studies in Iran, the reported infection rates of sheep mesenteric lymph nodes in various parts of Iran were as followed: Isfahan, 11% (Kheirabadi et al, 2015); Urmia, 65.7% (Yakhchali et al, 2009); Shiraz, 11.5% (Shekarforoush et al, 2004); Tabriz, 52.5% (Tavassoli et al, 2007) Kermanshah, 19.7% (Hashemnia et al, 2016). In this research, the infection rate of sheep in their mesenteric lymph nodes was 8.6%.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It should be noted that in this research, mesenteric lymph nodes of the sheep were examined because it is the first site that the parasite chooses to enter (Shekarforush & Arzani-Shahni, 2002). However, based on other conducted studies in Iran, the reported infection rates of sheep mesenteric lymph nodes in various parts of Iran were as followed: Isfahan, 11% (Kheirabadi et al, 2015); Urmia, 65.7% (Yakhchali et al, 2009); Shiraz, 11.5% (Shekarforoush et al, 2004); Tabriz, 52.5% (Tavassoli et al, 2007) Kermanshah, 19.7% (Hashemnia et al, 2016). In this research, the infection rate of sheep in their mesenteric lymph nodes was 8.6%.…”
Section: Discussionmentioning
confidence: 50%
“…Humans serve as either intermediate or final hosts and can be infected by both adult and nymph form of parasite; however, the infection with the former is rare. The two forms of the infection are: visceral linguatulosis, following consumption of water, vegetables or fruits contaminated with the eggs, and nasopharyngeal linguatulosis, known also as Halzoun or Marrara syndrome, following consumption of raw or undercooked infected viscera of infected animals (Shekarforoush et al, 2004;David et al, 2006;Tajik et al, 2006;Koehsler et al, 2011;Pirali Kheirabadi et al, 2014;Yazdani et al, 2014;Hajimohammadi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nourollahifard et al (2010) and Sadeghi-Dehkordi et al (2014) reported the prevalence of L. serrata nymphs to be significantly higher in females than in males. In similar studies in sheep and goats, there was found no significant differences between infection rate and gender (Kheirabadi et al, 2014;Azizi et al, 2015;Kheirabadi et al, 2015). They attributed this finding to the longer lifespan of female animals before being slaughtered.…”
Section: Discussionmentioning
confidence: 85%
“…In the first step of examination, the prevalence of L. serrata infection were detected 24.81% (100/403) (Rezaei et al, 2012;Youssefi et al, 2012;Sadeghi-Dehkordi et al, 2014;Kheirabadi et al, 2014), 9-52.5% in sheep (Tavassoli et al, 2007a;Nourollahifard et al, 2011;Youssefi et al, 2012;Sadeghi-Dehkordi et al, 2014;Azizi et al, 2015;Kheirabadi et al, 2015), and 14.8-69.1% in cattle (Tajik et al, 2006;Nourollahifard et al, 2010b;Youssefi and Hadizadeh-Moalem, 2010;Rezaei et al, 2011;Youssefi et al, 2012;Alborzi et al, 2013;Nematollahi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation